PROSES BERPIKIR SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA BERDASARKAN LANGKAH-LANGKAH POLYA DITINJAU DARIADVERSITY QUOTIENT - Widyastuti, Rany; Usodo, Budi; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aims of this research are to describe the thinking process of junior high school students with type of climber, camper, and quitter in solving mathematics problems based on Polyaâs rule. This was a qualitative descriptive research. The subjects of this research were taken by using a combined technique of stratified sampling and purposive sampling. The subjects of this research were three 9th grade student of SMP Negeri 1 Jaten Karanganyar regency, which consists of astudent with climberâs type, a student with camperâs type, and a student with quitterâs type. The data collection in this research was conducted through questionnaires and task-based interview technique whichwereused in the subject matter of two variable linear equation system.Thedata validationtechnique used triangulationof time andreferences. The data was analyzed by usingMiles and Hubermanâs concept, that was dataâs reduction, dataâs presentation, and conclusion. The result of this research showed that (1) climberâs student used assimilation thinking process in understanding the problem, devising a plan, carrying out the plan, and looking back the answer, (2) camperâs student used assimilation thinking process in understanding the problem, carrying out the plan, and looking back the answer, student used assimilation and accomodation thinking process in devising a plan, and (3) quitterâs student used imperfection assimilation and accomodation thinking process in understanding the problem, student didnât use assimilation and accomodation thinking process in devising a plan, carrying out the plan, and looking back the answer.Keywords: thinking process, problem solving, Polyaâs rule, Adversity Quotient (AQ)